Analysis of hearing impairment related to general health conditions in elderly people - Moraes-Crispim, Karla Geovanna (2013)
Self-reported health has been considered a helpful indicator of health conditions and certain outcomesin elderly people. An exploratory, descriptive and cross-sectional cohort study was conducted amongan elderly group randomly recruited at Unati/uea, Manaus, Amazonas State, Brazil. Data was collectedby structured questionnaires obtaining socio-demographic informations, and the functional evaluation.Subsequently were applied the Hearing Handicap Inventory for the Elderly Screening Version (hhie-s),and The Mini-Mental State Examination (mmse). The aged participants on this research mostly selfratedtheir health as good or reasonable, with rarer extreme self-assessments. Data from hhie-s levelsof hearing impairment was obtained 27 (33.35 %) with normal hearing, 31 (38.75 %) light hearingloss, 19 (23.75 %) moderate hearing loss; and 3 (3.75 %) severe hearing loss. Mean total mmse scoreof the study subjects was 23.47 points. Our results show compatibility with literature data, also, it isdenoted the health performance superior on these group of elderly.